2020
DOI: 10.1186/s41610-020-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Foraging behaviour and preference of pollen sources by honey bee (Apis mellifera) relative to protein contents

Abstract: Background: Pollen is an important source of protein and lipids for many animals including honey bees. In order to understand the foraging behaviour of honey bee colonies and preference among the available floral resources, pollen collections from three experimental healthy colonies of honey bees were analysed in the month of June. Results: The amount of pollen collections were related to the colony's need which was indicated by the number of larval and adult bees present in the hive. Interesting was the seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 35 publications
1
41
1
1
Order By: Relevance
“…Given the fact that 50% of active substances with a commonly used pollen collection methodology in 2016-2018 were found to have a coefficient of variation of 1 or higher, it was necessary to determine how often these substances could occur at one site when collecting pollen from multiple hives. Ghosh et al (2020) found in their study that bee colonies in different habitats collect different amounts of pollen, and, in individual colonies, pollen from different plant species was determined in different amounts. The differences may be related to the number of active fliers.…”
Section: Resultsmentioning
confidence: 99%
“…Given the fact that 50% of active substances with a commonly used pollen collection methodology in 2016-2018 were found to have a coefficient of variation of 1 or higher, it was necessary to determine how often these substances could occur at one site when collecting pollen from multiple hives. Ghosh et al (2020) found in their study that bee colonies in different habitats collect different amounts of pollen, and, in individual colonies, pollen from different plant species was determined in different amounts. The differences may be related to the number of active fliers.…”
Section: Resultsmentioning
confidence: 99%
“…The pollen foraging behaviour of bees is influenced by the following factors: abundance and diversity of floral resources [20], availability of pollen grains, season [21], time of the day, temperature, number of larvae present in the hive, amount of stored food, nutrient (especially protein) quality and quantity of the pollen [22], colour, shape, morphology and odour of the flower [23], health status of the bees [24], and nectar quality [25]. As bees collect pollen from a single plant species at a given time, colours of pollen loads are homogenous.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to protein content, the different effects of pollen diets on HG development could also be explained by other limiting factors, such as amino acids, lipids, and vitamins [ 37 ]. The protein content of pollen is a reliable and direct measure of pollen quality [ 11 ], and it was suggested as the first criterion for honey bee pollen-foraging preference [ 38 ]. However, our primary experiment showed that pear pollen and apricot pollen had comparable protein contents (2699 mg/kg and 2811 mg/kg, Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the report by Schmidt (1982), who showed that honey bee preference for pollen was not based on its protein content [ 39 ]. However, other studies have demonstrated that amino acid composition [ 40 ], phenolic contents [ 41 ], and protein contents [ 38 ] in pollen sources could all affect honey bee foraging preferences. Furthermore, olfactory and chemotactile stimulation also have the potential to influence honey bees’ pollen-foraging behavior [ 42 ].…”
Section: Discussionmentioning
confidence: 99%